Celebrity Endorsements: Influence and Effectiveness on consumers’ purchase intentions. - Devidasani, Neha (2010)
In today’s world, celebrity endorsements have become one of the most popular marketing techniques that advertisers opt for. Consumers today are fascinated and mesmerized by celebrities. Advertisers take advantage of this fascination and rope in celebrities such as movie stars, singers, athletes etc in endorsing their brand or product in order to influence the purchase decisions of consumers.